USING CHAIN MASSAGE GAME TO SUPPORT YOUNG LEARNERS’ VAK LEARNING STYLE - Yella Dezas Perdani (Universitas Lambung Mangkurat, 2021)
This research discusses the involving chain massage to accommodate young learners' learning style in which is conducted at grade 4 of one elementary school in Bandung. The aim of this research are (1) involving chain massage games in teaching English to the young learner, especially in grade 4 of an elementary school in Bandung, (2) finding out teacher’s and children’s responses toward the implementation of chain message in TEYL. This research uses a qualitative study where there are 40 students and one English teacher as the participants. The findings of this study show that chain messages can be considered as an effective activity of TEYL.The children seem to learn English more excitedly by game. With regard to the teacher, chain message game creates classroom activities more interesting and joyful because the children’s are involved in. Moreover, this game is also support different learning style of the children, visual, auditory and kinesthetic. However, the teachers found some obstacles in implementing the technique because they still children who easily get bored.